Atividade biológica dos óleos essenciais de plantas sobre isolados do complexo Cryptococcus neoformans - Mendonça, Ana Flávia (2015)
Cryptococcosis is an opportunistic fungal disease, caused by the yeasts from the Cryptococcus neoformans complex, frequently associated with high rates of morbidity and mortality. Patients infected with the human immunodeficiency virus (HIV), transplanted or in use of immunosuppressive therapies are the main affected. Fluconazole and amphotericin B, the main antifungals applied in the treatment of the disease, are toxic to the patient and, their use for prolonged time, has selected resistant strains making necessary to search for new compounds that shows good antifungal activity and low levels of toxicity. Thus, the essentials oils (EOs) from plants are promising for this purpose because their antimicrobial property has been already reported. This study aimed to evaluate the biological activity of EOs from Cinnamomum zeylanicum, Syzygium aromaticum, Juniperus virginiana, Rosa centifolia, Illicium verum and eugenol on fungal isolates from C. neoformans complex. Tests were carried out to evaluate the fungal activity, interaction with amphotericin B and fluconazole, time kill assay, mechanism of action and cytotoxicity. The EOs of C. zeylanicum and S. aromaticum and its majority compound, eugenol, presented the best antifungal activity with minimum inhibitory concentrations (MICs) ranging from 128-512 μg/mL and minimum fungicidal concentrations (MFCs) from 256-1024 μg/mL. The EO of S. aromaticum has an increase in its antifungal activity when combined with amphotericin B in all the isolates evaluated while the EO of C. zeylanicum and eugenol showed no changes of its activity when associated with drugs. The study of the mechanism of action revealed that C.zeylanicum, S. aromaticum and eugenol, in MIC, inhibited the synthesis of ergosterol and in MFC promoted membrane damage. The hemolytic activity assays showed low toxicity of these compounds. These results demonstrate action of the EOs from C. zeylanicum and S. aromaticum and eugenol against isolates of C. neoformans complex. Thus, these EOs become promising in the search for new drugs to be used in the treatment of cryptococcosis.